An Adverse Outcome Pathway for food nanomaterial-induced intestinal barrier disruption - Stanco, Deborah; Lipsa, Dorelia; Bogni, Alessia; Bremer-Hoffmann, Susanne; Clerbaux, Laure-Alix (Frontiers in Toxicology, 2024)
IntroductionThe ingestion of nanomaterials (NMs) may impair the intestinal barrier, but the underlying mechanisms remain evasive, and evidence has not been systematically gathered or produced. A mechanistic-based approach would be instrumental in assessing whether relevant NMs disrupt the intestinal barrier, thereby supporting the NM risk assessment in the food sector.MethodsIn this study, we developed an adverse outcome pathway (AOP) based on biological plausibility and by leveraging information from an existing NM-relevant AOP that leads to hepatic outcomes. We then extracted the current evidence from the literature for a targeted selection of NMs with high relevance to the food sector, namely, ZnO, CuO, FeO, SiO2, and Ag NMs and nanocellulose.ResultsWe propose a new AOP (AOP 530) that starts with endocytic lysosomal uptake, leading to lysosomal disruption inducing mitochondrial dysfunction. Mitochondrial impairments can lead to cell injury/death and disrupt the intestinal barrier. The evidence collected supports that these food-related NMs can be taken up by intestinal cells and indicates that intestinal barrier disruption may occur due to Ag, CuO, and SiO2 NMs, while only few studies support this outcome for FeO and ZnO. Lysosomal disruption and mitochondrial dysfunction are rarely evaluated. For nanocellulose, none of the studies report toxicity-related events.ConclusionThe collection of existing scientific evidence supporting our AOP linking NM uptake to intestinal barrier impairments allowed us to highlight current evidence gaps and data inconsistencies. These inconsistencies could be associated with the variety of stressors, biological systems, and key event (KE)-related assays used in different studies. This underscores the need for further harmonized methodologies and the production of mechanistic evidence for the safety regulatory assessment of NMs in the food sector.